Fraksinasi dan Potensi Antioksidan dari Ekstrak Protein Kasar dari Spons Haliclona sp Asal Perairan Spermonde Sulawesi Selatan - Warsidah, Warsidah; Sofiana, Mega Sari Juane; Safitri, Ikha; Nurdiansyah, Syarif Irwan (Journal of The Indonesian Society of Integrated Chemistry, 2023)
Sponge Haliclona Sp is a member of the phylum porifera class Demospongia which is found living in the waters of the spermonde coral reefs of South Sulawesi. Its interaction with various microorganisms that live in the waters causes the formation of various kinds of active compounds and biological activities that are important in the world of health. The purpose of this study was to extract and fractionate protein from the Haliclona Sp sponge from Spermonde waters through confirmation using ammonium sulfate at various antioxidant levels, and to determine the content and activity of the protein in each fraction. The results showed that the protein content and antioxidant activity (IC50) of each fraction were, among others, in fraction 1 (0-30%) of 0.143 mg/L and 78.11 mg/L, fraction 2 (31-50%) 0.045 mg/L and 153.55 mg/L, fraction 3 (51–70%) of 0.020 and 161.12 mg/L, and fraction 4 (71–90%) of 0.112 and 104.71 mg/L, while crude protein of 0.277 mg/L and 115.22 mg/L. Ascorbic acid as a positive antioxidant control in this study resulted in an antioxidant activity of 2.74 mg/L.